1994
DOI: 10.1093/ptj/74.9.845
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Time on Static Stretch on the Flexibility of the Hamstring Muscles

Abstract: The results of this study suggest that a duration of 30 seconds is an effective time of stretching for enhancing the flexibility of the hamstring muscles. Given the information that no increase in flexibility of the hamstring muscles occurred by increasing the duration of stretching from 30 to 60 seconds, the use of the longer duration of stretching for an acute effect must be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
194
6
49

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(266 citation statements)
references
References 3 publications
17
194
6
49
Order By: Relevance
“…The improvement of hamstring flexibility of the 3 groups is consistent with the findings of Bandy and irion [32] and the recent study by Cini et al [33], who reported that a 30-s static stretch was sufficient for increasing the hamstring flexibility. However, Berenbaum et al [34], who investigated whether 3 weeks of either static or dynamic hamstring stretching affected RoM and anaerobic exercise performance in recreationally active individuals, reported that there were no significant differences between groups for the horizontal jump, vertical jump, or 50-meter sprint.…”
Section: Discussionsupporting
confidence: 90%
“…The improvement of hamstring flexibility of the 3 groups is consistent with the findings of Bandy and irion [32] and the recent study by Cini et al [33], who reported that a 30-s static stretch was sufficient for increasing the hamstring flexibility. However, Berenbaum et al [34], who investigated whether 3 weeks of either static or dynamic hamstring stretching affected RoM and anaerobic exercise performance in recreationally active individuals, reported that there were no significant differences between groups for the horizontal jump, vertical jump, or 50-meter sprint.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have investigated the effects of stretching, and several reports have shown that this technique improves P-ROM [10][11][12] . Similar to these results, the present findings also showed an increase in P-ROM after MFR.…”
Section: Discussionmentioning
confidence: 99%
“…During the final stretch the subject was instructed to place his or her great toe on the wall and lean forward to stretch the fascia directly (Fig 4). 13,[17][18][19] Group 1 received LED that was applied over the two most painful points on each subject's plantar fascia. The parameters chosen for this intervention were 12 J/cm 2 applied for 4.56 minutes, over each treatment point.…”
Section: Methodsmentioning
confidence: 99%